Collaborative Inquiry with Men Who Use Intimate Partner Violence: Service User Perspectives on Expertise in Domestic Violence Services for Men - Jury, Rebecca (Journal of family violence, 2023)
Concerns have been expressed regarding the efficacy of services for heterosexual men who use intimate partner violence. In addition, there has been limited research into the perspectives of these men regarding their use of services. The Australian study outlined in this article sought to examine the experiences of heterosexual men who use intimate partner violence (IPV) when they access domestic violence services. Collaborative inquiry was undertaken with men who were attending a residential domestic violence service to explore the research question; What does expertise look like in domestic violence services for men? When discussing expertise, twenty men identified four themes: lived experience and book knowledge, services and supports, professional helping skills and expertise, and non-professional helping and expertise. These collaborative researchers described expertise as a product of book knowledge and lived experience knowledge, indicating these knowledges could be located within the one person or shared between professionals and service attendees. The informants suggested cultural mentoring, peer support and co-production are important inclusions in men’s domestic violence services. They also highlighted positive peer affirmations as supporting their behaviour change and suggested sociological frameworks are central to successful interventions with men. Men who use IPV may have important insights about expertise in domestic violence services for men which can inform future practice.